2019
DOI: 10.1002/pam.22131
|View full text |Cite
|
Sign up to set email alerts
|

Is Information Enough? The Effect of Information about Education Tax Benefits on Student Outcomes

Abstract: There is increasing evidence that tax benefits for college do not affect college enrollment. This may be because prospective students do not know about tax benefits for college or because the design of tax benefits is not conducive to affecting educational outcomes. We focus on changing awareness of tax benefits by providing information to students or prospective students. We sent e‐mails and letters to students that described tax benefits for college, and we tracked college outcomes. For all three of our samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 52 publications
3
55
0
2
Order By: Relevance
“…In addition, applicants are disqualified if their assets (excluding housing value and retirement funds) exceed specific limits, though this impacts few students. 9 Our sample uses only the set of people who applied for a Cal Grant. We estimate that this sample represents approximately 50 percent of college-bound seniors in California, and hence a large group of considerable interest (see footnote 3).…”
Section: A Overview Of the Cal Grant Programmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, applicants are disqualified if their assets (excluding housing value and retirement funds) exceed specific limits, though this impacts few students. 9 Our sample uses only the set of people who applied for a Cal Grant. We estimate that this sample represents approximately 50 percent of college-bound seniors in California, and hence a large group of considerable interest (see footnote 3).…”
Section: A Overview Of the Cal Grant Programmentioning
confidence: 99%
“…In addition, a student or their family must also have sufficient "unmet financial need," which is calculated based on a student's potential expenses and expected family contributions. 11 We ignore this 9 During our sample period, dependent students and independent students with dependents were disqualified if they had assets (excluding housing value) exceeding $42,000-$49,600 (depending on the year). Independent students without dependents (other than a spouse) were required to have assets below $20,000-$25,110 (depending on the year).…”
Section: A Overview Of the Cal Grant Programmentioning
confidence: 99%
“…In spite of early positive evidence suggesting positive enrollment effects, new research has shown less consistent and positive effects on enrollment (e.g., Bergman et al, 2019;Phillips & Reber, 2018). In addition to inconsistent average effects, new estimates suggest that messages may be differentially effective by institutional context (e.g., community versus 4-year colleges; Castleman & Page, 2016) or student background (e.g., language spoken at home; Phillips & Reber, 2018).…”
Section: Behavioral Economics and Text Messaging As An Informational mentioning
confidence: 99%
“…Policymakers and civil servants aiming for policies that lead to behavior change face constraints including limited budgets, staff time, and an inattentive public. For example, one messaging intervention that disseminated information about the tax benefits for college among high school seniors was intended to boost college enrollment but did not affect enrollment rates (Bergman, Denning, & Manoli, 2019). In another study where high school seniors participated in mock college application workshops, enrollment rates did increase (Oreopoulos & Ford, 2019).…”
Section: Theorymentioning
confidence: 99%